Juridical Review of Taxpayer Data Protection in Cases of Misuse of Digital Tax System Access - Judijanto, Loso; Sukma, Ahmad Novindri Aji (PT. Anagata Sembagi Education, 2025)
The development of information technology has driven a significant transformation in the tax administration system in Indonesia through the digitization of services such as e-filing, e-billing, and the integration of NIK as an NPWP. This modernization aims to increase efficiency, transparency, and compliance, but at the same time poses serious risks in the form of leakage and misuse of taxpayers' personal data. Tax data is very sensitive because it includes identity, financial information, economic transactions, and compliance records, which in Law No. 27 of 2022 concerning Personal Data Protection (PDP Law) is categorized as specific data with high protection standards. In the legal context, the protection of taxpayer data is strengthened by Article 28G paragraph (1) of the 1945 Constitution and Article 34 of the KUP Law which requires tax officials to maintain confidentiality. The Directorate General of Taxes (DGT) as a data controller has the obligation to manage data in a legal, proportionate, and secure manner by implementing encryption, access control, and incident notification mechanisms. Failure to carry out these obligations can have administrative, civil, and criminal consequences. This study uses a normative juridical method with a statutory and conceptual approach to assess the effectiveness of taxpayer legal protection in digitalization. The results of the study emphasized the importance of harmonizing the PDP Law and the KUP Law as well as strengthening the DGT institution so that legal protection is more comprehensive, transparent, and able to maintain public trust in the digital tax system.